Catalytic conversion of gaseous tar using coal char catalyst in the two-stage downer reactor. (1st March 2022) - Jiang, Yuan; Zong, Peijie; Bao, Yuan; Zhang, Xin; Wei, Haixin; Tian, Bin; Tian, Yuanyu; Qiao, Yingyun; Zhang, Juntao
Abstract: The effect of catalyst height (0–50 mm) and catalyst temperature (600–900 °C) on the catalytic cracking of gaseous tar is investigated using a two-stage down reactor. Results show that the utilization of catalyst promotes the removal of coal tar. The yield of coal tar at the pyrolysis temperature of 900 °C is 7.14% and tar is composed of aromatics and high-carbon-number aliphatics. The coal char prepared by fast coke-making method at 900 °C is directly used as a catalyst in the catalytic cracking of coal tar. When the catalyst temperature and the catalyst height are 900 °C and 50 mm, the tar produced by coal pyrolysis is connected with high-temperature coal char for a short time, reducing the tar yield from 7.14% to 4.26%. Among them, aliphatic hydrocarbons with carbon number of C10 and C11 and aromatics are the main components of coal tar. Similarly, compared with the pyrolysis, the content of CH4 and H2 obtained with the addition of the catalyst increase from 0.56 to 0.97 to 1.64%g/g coal and 1.02%g/g coal, respectively. Moreover, GC/MS results show that the increment of catalyst height and catalyst temperature increases aromatics content and facilitates the conversion of high-carbon-number component to low-carbon-number ones. Highlights: The char produced by coal pyrolysis is directly used as a catalyst in the catalytic cracking of gaseous tar. The short-time contact between tar with high-temperature coal char reduces the yield of tar. The yield and composition of gas and tar with the addition of char change significantly. Attempt to propose the mechanism of tar catalytic cracking process over char catalysts.